Personality and social responsiveness in autism spectrum disorders and attention deficit/hyperactivity disorder - Poustka, L.; Bender, F.; Bock, M.; Bölte, Sven; Möhler, E.; Banaschewski, T.; Goth, K. (2011)
Objectives: This study addresses the question whether personality dimensions differ between children with autism spectrum disorders (ASD) and attention deficit/hyperactivity disorder (ADHD), and whether these personality characteristics influence social problems in these groups of children. Methods: 68 children with ADHD (n = 32) and ASD (n = 36) were assessed with the Junior Temperament and Character Inventory (JTCI 7-11 R) and the Social Responsiveness Scale (SRS), as rated by the parents. Diagnosis of ASD was confirmed with standardized diagnostic instruments (ADOS und ADI-R). Results: Both children with ASD and ADHD displayed significantly decreased scores in persistence, self-directedness and cooperativeness compared to normative values. Additionally, children with ASD showed extremely low reward dependence and differed significantly from children with ADHD in the temperament dimensions harm avoidance and reward dependence as well as in the character dimensions self-directedness and cooperativeness. In both groups, personality dimensions, especially reward dependence, were predictive of social responsiveness, as assessed by the SRS. Conclusion: The results suggest that specific personality characteristics are present already in young children with ASD and ADHD and may have an impact on their social competence.